Refleksje o języku i słowie w pracy "O litewskich i polskich prawach..." autorstwa Tadeusza Czackiego = Reflections on language and words in the work "About Lithuanian and Polish Laws..." by Tadeusz Czacki - Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains an analysis of information on languages, including the former Polish language, contained in the work "About Lithuanian and Polish Laws..." by Tadeusz Czacki from 1801. The elaboration of the former rights the scholar enriched with many discussions on the meaning of words, he included a number of reflections related to the emergence and trans- formation of the tribal communities, also seen through the prism of language use.
Keywords: język; historia; prawo; narracja; language; history; law; narration